2016
DOI: 10.1186/s13148-016-0230-5
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood methylation profiling of female Crohn’s disease patients

Abstract: BackgroundCrohn’s disease (CD) is a chronic inflammatory disorder belonging to the inflammatory bowel diseases (IBD). CD affects distinct parts of the gastrointestinal tract, leading to symptoms including diarrhea, fever, abdominal pain, weight loss, and anemia. The aim of this study was to assess whether the DNA methylome of peripheral blood cells can be associated with CD in women.MethodsSamples were obtained from 18 female patients with histologically confirmed ileal or ileocolic CD and 25 healthy age- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 67 publications
4
35
0
Order By: Relevance
“…PTPRN2 encodes a protein tyrosine phosphatase implicated in various biological processes including tumor pathogenesis and autoimmune disease [31][32][33][34]. Supporting our present findings, PTPRN2 has previously been reported to be the most significant DMP in PBMCs from patients with CD [19]. Interestingly, PTPRN2 shows dysregulated DNA methylation in obese children [31], pointing to a link between metabolic dysfunction and immune response.…”
Section: Differentially Methylated Positions In Patients With Crohn'ssupporting
confidence: 88%
See 2 more Smart Citations
“…PTPRN2 encodes a protein tyrosine phosphatase implicated in various biological processes including tumor pathogenesis and autoimmune disease [31][32][33][34]. Supporting our present findings, PTPRN2 has previously been reported to be the most significant DMP in PBMCs from patients with CD [19]. Interestingly, PTPRN2 shows dysregulated DNA methylation in obese children [31], pointing to a link between metabolic dysfunction and immune response.…”
Section: Differentially Methylated Positions In Patients With Crohn'ssupporting
confidence: 88%
“…Also, epigenetic modifications to hASCs might be reflected in peripheral blood, as already demonstrated in other inflammatory diseases such as obesity [45]. Indeed, changes to the PBMC methylome in CD have previously been described, revealing that differentially methylated genes implicated in immune response are the most frequently affected [19,46]. In agreement with these reports, we found the same enriched GO terms in hASCs in CD such as immune response and immune system process, and we found that some of the changes found in hASCs were replicated in PBMCs, even when patients were classified according to clinical status.…”
Section: Verification Of Candidate Genes In Circulating Pbmcs In Patimentioning
confidence: 71%
See 1 more Smart Citation
“…Folate and other methyl-donor molecules play a crucial role in the maintenance of epigenetic marks such as DNA methylation. The importance of the epigenetic component in the etiology of CD has recently been illustrated by the demonstration of modified DNA methylation profiles in patients compared to healthy subjects 5 , 7 , 9 , 12 , 42 . Furthermore, polymorphisms in the DNMT3a gene (involved in the establishment of de novo DNA methylation marks) were previously associated to an increased risk to develop CD, suggesting an important role of DNA methylation in the inflammatory process 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, the presence of DNA methylation in the promoter area is often inversely correlated with gene expression [9][10][11], which in certain cases was found to be a causal relationship [12,13]. Previous epigenetic studies reported differences in the DNA methylome of peripheral blood or peripheral blood mononuclear cells (PBMCs), with differentially methylated loci occurring in genes associated with inflammatory pathways [14][15][16]. Here, we sought to build on the previous studies by focusing on an individual immune cell type: monocytes.…”
Section: Introductionmentioning
confidence: 99%